ELEMENT OPTIMISATION TECHNIQUES TO MANAGE MULTIPLE DB BRIDGE PROJECTS IN EAST MALAYSIA - C.T, Ramanathan; Sambu Potty, Narayanan; M. Taharin, Radzif (2008)
The construction process and success in management of multiple bridge projects directly relies on the selection and optimization of their elements / components. Many problems will be avoided if the construction knowledge and experience are utilised during the selection of the bridge elements in the Design and Build (DB) process. A systematic selection process is required during design stage to maximise the use of available resources that will be suitable in respective locations. The relevant studies of multiple bridge designs consider and incorporate practical suggestions from the field personals.